A Longitudinal Study on International Students’ Stress, Problem Focused Coping and Cross-Cultural Adaptation in China 来华留学生跨文化压力应对和适应研究 - English, Alexander; Chi, Ruobing (Journal of International Students, 2020)
We conducted a longitudinal study to explore how the relationship between perceived cultural distance, stress- and problem-focused coping strategies may influence socio-cultural adaptation for international students in China. We collected longitudinal data on overseas students during the Fall semester of September 2013. Data were recollected 90 days later. The results show that: (1) perceived cultural distance did not predict the outcome of socio-cultural adaptation; (2) non-Asian students used more problem-focused coping strategies than Asian students; (3) interaction effect between stress, coping strategy and culture of origin is significant: for non-Asian students, problem-focused coping strategies alleviated the negative impact of stress on adaptation; and for Asian students, problem-focused coping strategies exacerbated the negative impact of stress on adaptation.有研究显示个体和集体主义文化背景下，人们应对跨文化适应压力的方式不同，但目前还缺乏在非西方背景下对相关结论的验证。因此，本研究以来华留学生为研究对象，采用纵向设计，探究了文化距离、压力和问题应对策略与社会文化适应之间的相关关系。研究对象为121名在华留学生（亚洲人=52人，非亚洲人=69人），数据收集间隔90天。研究发现：(1) 感知文化距离不能预测社会文化适应结果；(2) 非亚洲留学生相比亚洲留学生使用更多问题中心应对策略；(3) 压力X应对X种族的交互效应显著：对非亚洲群体，问题中心应对策略能够缓解压力对于适应的消极影响；而对亚洲群体而言，问题中心应对策略加剧了压力对于适应的消极影响。